The dawn of solar power in Brazil: current state and future challenges - Held, Gerrit Simon Rudolf (2017)
As a sun-soaked South American giant with a population of more than 200 million, Brazil is considered to have some of the best conditions for solar power worldwide. Despite its tremendous potential, the countryhas so far been rather slow indeveloping the national solar power market. After a devastating energy crisis in its draught afflicted hydroelectric sector, the dawn of solar power seems on the horizon.With the goalof diversifying its energy mix, Brazil initiated the large-scale deployment of solar power in 2014. Three years after its commercial commencement,the solar energy drive is stalled and policy efforts seem trivial under deteriorating political and economic conditions. As a comprehensive analysis of the industry’s state of affairsis currently insufficiently portrayed, this paper attempts to fill thisgap by discussing the latest solar market developments and outlining the progress and status of Brazil’s solar energy market objectives. While the findings prove a significant discrepancy betweenthe desired and achieved progress, this paper also finds that there is reason to be optimistic that the solar market growth will be unleashed in the future. As such, the analysis focuses on the critical state of the Brazilian solar market in 2017 and showcases the underlying challenges of transforming an energy sector during a recession.